Survival and Neurodevelopmental Outcomes Among Periviable Infants. Issue 7 (July 2017) - Younge, Noelle; Goldstein, Ricki F.; Bann, Carla M.; Hintz, Susan R.; Patel, Ravi M.; Smith, P. Brian; Bell, Edward F.; Rysavy, Matthew A.; Duncan, Andrea F.; Vohr, Betty R.; Das, Abhik; Goldberg, Ronald N.; et al.
Abstract : (Abstracted from N Engl J Med 2017;376:617–628) The purpose of this study was to evaluate survival and neurodevelopmental outcomes among periviable infants (born at 22–24 weeks of gestation) assessed at 18 to 22 months of corrected age. In the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Neonatal Research Network (NRN) alone, this improvement has been documented for over 2 decades now with increasing survival of infants born after 2008 at 23 to 24 weeks of gestation.